Modeling of heat absorption curves for ligand-competitor-DNA triple system - Dukhopelnikov, E. V. (Biophysical Bulletin, 1970)
The model for a ligand-competitor-DNA triple system is suggested. The model is based on chemical equilibria equations and allows one to analyze DSC experimental data. It is shown that the competitor addition alters the percentage of ligand bound to DNA both at room temperatures and at temperatures close to the melting temperature of DNA. Given the same binding constants and binding sites determined at room temperatures, both qualitative and quantitative differences in calorimetric melting curves can be detected depending on the enthalpy of binding.